Two-stage posterior spinal fusion for early-onset scoliosis: Two case reports. Issue 9 (March 2019) - Uehara, Masashi; Takahashi, Jun; Kuraishi, Shugo; Ikegami, Shota; Futatsugi, Toshimasa; Oba, Hiroki; Takizawa, Takashi; Munakata, Ryo; Koseki, Michihiko; Kato, Hiroyuki
Abstract: Rationale: Fusionless techniques for early-onset scoliosis (EOS) have evolved to allow near-normal growth while maintaining the correction achieved during the initial surgery. However, such procedures require repeated surgeries and have increased complication rates. We have developed a 2-stage fusion technique using pedicle screws for EOS to reduce patient burden and complication risk. This series describes the clinical and radiological features of 2 patients with EOS who received 2-stage posterior spinal fusion. This surgical method for EOS represents the first of its kind. Patient concerns: Case 1 was a 10-year-old girl who was diagnosed as having scoliosis with Prader Willi syndrome at the age of 2 years. Her preoperative major curve Cobb angle was 100 degrees at age 10 years. Case 2 was an 11-year-old boy who was found to have scoliosis with 22q11.2 deletion syndrome at the age of 4 years. His preoperative major curve Cobb angle was 77 degrees at age 11 years. Diagnosis: Whole-spine radiographs were performed to diagnose scoliosis. Interventions: Both patients received 2-stage posterior spinal fusion. Outcomes: Postoperative Cobb angle of the major curve improved to 46 and 48 degrees, respectively. Thoracic height respectively improved from 160 and 148 mm before surgery to 206 and 211 mm at final follow-up. Surgical outcome as evaluated by Scoliosis Research Society-22 patient questionnaires revealed acceptable results without any severe complications. Lessons: Based on the present case report, 2-stage posterior spinal fusion for EOS achieves good radiological and clinical outcomes without severe complications.